Indonesian Crimmigration Law: Critics of Immigration’s Law Enforcement Towards Illegal Expatriate Workers as The Impacts of Pro-Investment Policy - Hasmiati, Rahmatullah Ayu; Ardha, Dea Justicia; Priyambada, Galih; Gumilang, Arvin; Derei, Daniël (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study examines the characteristics of Crimmigration law in Indonesia and the use of the concept of law enforcement towards illegal foreign labor. This research is doctrinal research using inductive-deductive logic using library materials. The data was then analyzed using qualitative methods. The results showed that First, the characteristics of Crimmigration Law in Indonesia, can be seen from the selective policy used to select the foreigners who will enter into Indonesian Authority and the penal sanction which rooted in the Immigration regulations and Indonesian Law. The end of law enforcement toward the defendant is imprisonment and deportation. Second, the implementation of the Crimmigration law toward illegal foreign workers in Indonesia only uses immigration regulation without regard to labor regulations. Third, the enforcement-only focuses on residential permit abuse and sentencing for minimum punishment, not the working permit or doing an illegal activity such as illegal labor. Hence, critics emerge to urge the legal review of the related regulation with Crimmigration to achieve the main purpose of the law itself, law must be the first indicator to control people’s behavior as an Allien in foreign and the possible offenses threats can be reduced significantly.